The stepped model of peer provision practice: capturing the dynamics of peer support work in action - Zeng, Grace; Chung, D. (Pier Professional Ltd., 2018)
© 2018, Emerald Publishing Limited. Purpose: In recent years, the employment of peer providers (PPs) has grown with the wider acceptance of lived experience expertise in recovery-oriented service provision. Although its effectiveness, theoretical foundations and factors influencing outcomes have been studied, a framework accounting for the dynamics of the PP–peer relationship has yet to be formulated. The purpose of this paper is to employ a qualitative approach to explore the journeys undertaken by PPs with their peers and form it into a cohesive framework of understanding. Design/methodology/approach: In-depth interviews were conducted with PPs who were employed specifically to use their lived experience in supporting someone through mental distress. These interviews were recorded, transcribed and coded using a framework approach. To enhance rigour, this framework was verified with the latter author and three other participants recruited after data analysis. Findings: A stepped model of peer provision practice was crafted to capture the non-linearity of recovery, as well as the PP–peer relationship. This model is founded upon trust in the milieu of shared experience and involves: creating a safe place – a stage of building trust and rapport to a point where a PP is given permission to enter into their peer’s headspace; a working partnership – stage of setting and working towards goals collaboratively; and stepping out – a stage marked by the termination of the PP–peer relationship. Originality/value: This paper proposes a tangible framework underpinning the dynamics of peer provision practice, which furthers our understanding and complements current practice models in peer provision services.